Developing E-LKPD based on Creative Problem Solving to Enhance Higher Order Thinking Skills and Learner Autonomy in Topics Related to Progressive and Standing Waves - Rachmah, Diah Nur; Widiatmono, Restu (STKIP Singkawang, 2025)
This study aims to produce a valid, practical, and effective E-LKPD utilizing Creative Problem Solving (CPS) approach to enhance both Higher Order Thinking Skills (HOTS) and the independent learning attitude of students in topics related to progressive and standing waves. The research method employed was Research and Development utilizing the 4-D development design model, which includes the phases: Define, Design, Develop, and Disseminate; however, Disseminate phase was not implemented. The validity of the E-LKPD CPS was assessed by material and media validators. Its practicality was evaluated based on the feasibility of implementing the E-LKPD CPS during the learning process as observed. The effectiveness of the E-LKPD CPS was determined through N-gain tests, while user response was gathered via response questionnaire. Data analysis was conducted using quantitative descriptive methods. The E-LKPD CPS was pilot-tested in a limited setting at MAN 2 Yogyakarta, involving 33 MIPA 1 as experimental group and another 33 as control group (MIPA 2). The E-LKPD CPS received validity scores of 97.47% from content experts and 95.48% from media experts, both considered very valid. Its practicality scored at 84.08% (good). The effectiveness of the E-LKPD CPS in enhancing HOTS was demonstrated with experimental group N-gain of 70.69%, compared to the control group's 63.70%, both deemed moderately effective. The effectiveness in fostering independent learning attitudes yielded N-gain of 74.28% for the experimental group and 67.23% for the control group, also rated as moderately effective. Student response was highly favorable at 91.33% (very good). Consequently, the developed E-LKPD CPS is declared valid, practical, and effective for implementation in educational settings.